EVALUASI KEBIJAKAN PENGADAAN ENERGI LISTRIK UNTUK DAERAH TERDEPAN, TERLUAR, DAN TERTINGGAL (3T) DI DESA SELAUT KECAMATAN BUNGURAN BARAT KABUPATEN NATUNA TAHUN 2014-2022 - Jumiati, Sefi; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Electrical Energy Program is one of the central programs that has been implemented in Selaut Village, West Bunguran District, Natuna Regency. Based on Presidential Decree no. 63 of 2020 concerning Determination of Disadvantaged Regions 2020-2024, there are 62 districts that are included in the 3T region category and one of them is Natuna district. Starting from the problem of electrical equipment that is outdated and damaged, causing frequent power outages and hampering the activities of the Selaut Village community. This research aims to find out and analyze, evaluate electricity procurement policies for frontier, outermost and disadvantaged areas (3t) in Selaut Village, West Bunguran District, Natuna Regency in 2014-2023. The theory used as a reference is the indicators from M. Steers, namely size and policy objectives, understanding of a program, accuracy of targets, timeliness, achievement of a goal and visiblechanges. The research method used is a qualitative method. From the results of research that the author has conducted regarding the electricity procurement policy in Selaut Village, which is classified as a 3T area, a conclusion can be drawn that the effectiveness of electricity procurement policies in 3T areas, one of which is Selaut Village, has not running effectively, this can be seen from the indicators related to policy effectiveness, namely , understanding the program, accuracy of targets, timeliness, achievement of goals and real changes. The supporting factor in implementing this policy in Selaut Village is that there is good coordination between state officials in carrying out activities. Then there are also inhibiting factors in the distribution of this policy, namely the lack of updates to existing PLTS equipment, uncertain repair assistance, resulting in frequent internal power outages, as well as limited facilities and access to the island and unpredictable bad weather. Keywords: Evaluation, Policy, 3T Regional Electrical Energy